PENGARUH RETURN ON ASSET, RETURN ON EQUITY, RETURN ON INVESTMENT, DAN DEBT TO EQUITY RATIO TERHADAP HARGA SAHAM PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Syafruddin Syafruddin (Universitas Riau Kepulauan, 2017)
This study intense to determine the financial performance of (Return on Assets (ROA), Return on Equity (ROE), Return on Investment (ROI), and the Debt to Equity Ratio (DER)) on stock prices either partially or simultaneously. The Object of study focused on manufactured companies listed on the PT. Indonesia Stock Exchange (BEI) in the period 2007-2011. The selection of samples based on purposive sampling, and database achieved from 12 company sectored on manufactured business. The results of this study indicate that, the variable ROA and the ROE has an influence on stock prices. While other independent variables, namely ROI and DER have no effect on stock prices. Simultaneously, all independent variables ROA, ROE, ROI, and the DER has an influence on stock prices.